The Impact of the SAPUKU Program on the Economic Empowerment of Local Communities in Kuningan Regency: Plastic Waste Management as a Sustainable Solution - Rohimi, Upit Elya (Al-Makki Publisher, 2025)
The environmental crisis triggered by plastic waste has become a global problem that threatens the sustainability of ecosystems and human health. Accumulated plastic waste causes damage to flora and fauna, disrupts marine and terrestrial ecosystems, and exacerbates climate change. At the local level, Kuningan Regency faces similar challenges by producing 121,940.66 tons of waste per day in 2015. The SAPUKU program launched by the Kuningan Regency Government aims to address this problem through a collective approach that involves all elements of society. This research aims to analyze the impact of the SAPUKU program on the economic empowerment of local communities and identify its success factors. The research method used is qualitative with descriptive design, collecting data through surveys and interviews. The results showed that the program successfully increased community income through the management of recycled plastic waste, increased environmental awareness, and strengthened community involvement. However, challenges related to recycling facilities and infrastructure are still obstacles that need to be improved. This research contributes to the development of community-based waste management policies, supports the circular economy, and enriches the theory of environment-based economic empowerment.